Ethnobotanical Attributes and Phytochemical Analysis of Food Grains of District Chamba, Himachal Pradesh: Ethnobotany and phytochemistry of Chamba food grains - Kumari, Dimple; Thakur, Neha; upmanyu, sachin (Journal of Cereal Research, 2025)
Millets, ancient and resilient cereal crops, have regained prominence because of the high nutritious value and compliance to challenging climatic settings. They are now known as Nutri-cereals because of their high protein, vitamin, and mineral content, despite previously being overlooked in favor of crops like wheat and rice. Particularly in dry and semi-arid parts of Africa and Asia, where they are used as staple foods and animal feed, millets are vital to food security. This paper focuses on traditional food grains from Chamba, Himachal Pradesh, emphasizing millets e.g. foxtail millet and finger millet, along with pseudocereals like amaranth, buckwheat, and quinoa. These crops serve as crucial staples in this region, offering significant nutritional benefits including rich protein, fibre, and mineral content. Their ability to grow in degraded soils and tolerance to water stress renders them quite suitable candidates for combating food insecurity, particularly in arid regions. The study highlights the ethnobotanical importance of these crops, not only as food sources but also in cultural and medicinal practices. Millets, known for being gluten-free, offer essential benefits like diabetes management and cardiovascular support. The presence of advantageous substances including alkaloids, flavonoids, and saponins in traditional grains is shown by phytochemical analysis, which adds to their health-promoting qualities. The ethnobotanical survey conducted in Chamba reveals that local communities have long relied on these crops for food, nutrition, and various traditional practices. The findings underscore the role of these grains in preserving local culture, ensuring food security, and promoting sustainable agriculture. With advancements in agronomy, these traditional grains hold the potential to become superfoods, supporting Sustainable Development Goals (SDGs) like zero hunger and good health.